ANTIMYCOBACTERIAL EVALUATION OF FIFTEEN MEDICINAL PLANTS IN SOUTH AFRICA - Mmushi, T. J.; Masoko, P.; Mdee, L. K.; Mokgotho, M. P.; Mampuru, L. J.; Mampuru, R. L. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Fifteen plant species were collected from the Nelspruit Botanical Garden based on a list of plants provided by Phytomedicine Programme at the University of Pretoria and their ethnopharmacological information. Hexane, dichloromethane (DCM), acetone and methanolic extracts were screened for antimycobacterial activity against Mycobacterium smegmatis. The acetone extract of Milletia stulhimannii was the most active, showing activity against Mycobacterium smegmatis with minimum inhibitory concentration (MIC) value of 0.13 mg/ml. Acetone extracts for all plants had lower MIC values ranging between 0.11-1.25 mg/ml against M. smegmatis. Milletia stulhimannii, Albizia gummifera, Xanthocercis zambesiaca and Barringtonia racemosa have shown great potential as anti-tuberculosis agents. They were active against M. smegmatis with average MIC values of acetone extracts of 0.13 mg/ml.